Removal of Sr2+ using high-surface-area hydroxyapatite synthesized by non-additive in-situ precipitation - Kim, J. (2019)
Owing to their high-risk factor, many attempts have been made to remove radionuclides from water. Sr2+ ions are the target of removal by synthesized hydroxyapatite in this research. A facile method for synthesizing high-surface-area hydroxyapatite by in-situ precipitation using excess diammonium phosphate solution and without any additive was developed. The highest surface area achieved using this method was 177.00 m2/g, and the synthesized hydroxyapatite was also mesoporous. The effects of different pH, temperatures, and ion concentrations during synthesis on the properties of the hydroxyapatite were assessed, and it was found that a low temperature and high pH were optimal for synthesizing high-surface-area hydroxyapatite. The maximum strontium removal capacity of 28.51 mg/g was achieved when the pH-7.5 solution was used. This performance is competitive in comparison with previously developed synthesized materials. Synthesized hydroxyapatite could effectively remove radioactive strontium from an aqueous solution for nuclear waste management. Â© 2018 Elsevier Ltd